Mediation in the Church: A Review of the Literature and the Key Elements of Mediation - Roseman, Daniel (Studia canonica, 2013)
The Author identifies the key elements of mediation in terms of goals, practices and processes, and then reviews the relevant canons and canonical literature to assess how these key elements are used in ecclesiastical mediation processes. The goals of mediation—the reconciliation of disputants’ interests and the restoration of relationships—are in harmony with canon law and Christian principles. Formal trials and administrative procedures are to be the last resort for resolving disputes in the Church. Canons 1466 and 1713-1715 deal with mediation as an alternative to litigation, and c. 1733 with mediation as an alternative to administrative recourse. Many ecclesiastical disputes lend themselves to mediation, although it is little used in the Church, despite its demonstrated benefits. The Author discusses, inter alia, the advantages and disadvantages of the apparent preference in the Church for 'insider partials' instead of detached outsiders as mediators.